Thoughts Of Madzhab Imams About Corruption And Its Sanctions (Preventive Measures Against Corruption) - Dedi (Fakultas Agama Islam Universitas Wiralodra, 2023)
This research was done to find out what Imams of Madzhab thought about corruption and what their basic beliefs were. Normative juridical research was used to study this, and the conclusion was that corruption violates sharia. Shari'a Islam aims to protect human health by ensuring that what is called maqashidussy syaria'ah is realized. In broader terms, corruption practices go against principles of fairness, accountability, and responsibility. Corruption can have a negative impact on the life of the state and society, leading to damage in advance. The rationale for punishment for perpetrators of corruption according to the Imams of Madzhab is to place corruption in the category of takzir takzir. Takzir is a legal sanction that is imposed on a person who commits a crime that violates both Allah's rights and human rights. This form of sanction is not explicitly determined in the texts of the Quran and hadith, because no specific determination has been made. This means that the decision to impose it is left to the discretion of the judge or local authorities. Takzir legal sanctions can take a number of forms, such as imprisonment, ending punishment, entering a list of people, or legal dismissal.